Development and Comparison of a Novel Mid‐Region Directed p‐Tau 181 Assay with Tau Positron Emission Tomography in Alzheimer’s Disease - Tagai, Kenji; Tatebe, Harutsugu; Matsuura, Sayo; Zhang, Hong; Kokubo, Naomi; Matsuoka, Kiwamu; Endo, Hironobu; Oyama, Asaka; Hirata, Kosei; Shinotoh, Hitoshi; Kataoka, Yuko; Matsumoto, Hideki; et al. (Alzheimer's & dementia, 2023)
Background Several blood‐based phosphorylated tau (p‐tau) assays that focus on the N‐terminus have been developed and established as non‐invasive biomarkers for detecting Alzheimer’s disease (AD) pathologies from their early stages. However, the p‐tau measured by these assays may not necessarily reflect the accumulation of tau lesions in the brain due to correlation with Aβ burden. Therefore, there remains a significant unmet need to develop blood‐based tau biomarkers that are interchangeable with tau deposits in the brain. Methods We have devised a novel Simoa assay that can detect N‐ and C‐terminally truncated fragment of p‐tau181 in plasma (QST assay), utilizing an antibody against the mid‐region of tau protein for capture, and an antibody AT270 for detection. The plasma p‐tau181 was measured with both the QST assay and a conventional p‐tau181 Simoa assay (Quanterix) in 164 subjects, including 40 cognitively normal (CN) individuals, 48 with AD continuum, 50 with progressive supranuclear palsy, and 26 with other frontotemporal lobar degeneration, who underwent Aβ (11C‐PiB) and tau (18F‐PM‐PBB3, Florzorotau) positron emission tomography (PET) scans. Subsequently, we conducted a head‐to‐head comparison of p‐tau181 assays in correlation with the imaging biomarker and cognitive dysfunction. Results QST p‐tau assay demonstrated inferior performance compared to the Quanterix assay in the qualification of Aβ PET (QST assay: AUC = 0.771, Quanterix assay: AUC = 0.867). Neither assay showed a significant correlation with Aβ PET accumulation in the AD group. Meanwhile, the QST assay exhibited excellent correlations with tau PET accumulation in regions indicative of AD including temporal cortex and neocortex (p<0.0005), whereas the Quanterix assay demonstrated non‐linear correlations with tracer binding. In trajectories from CN to AD continuum, the QST assay exhibited a linear association, as well as tau PET accumulation, while the Quanterix assay exhibited a sigmoidal curve association. Conclusions We have developed a new p‐tau181 assay directly correlated with tau PET accumulation. This quantitative system serves as a promising surrogate marker for tau lesions in the AD brain, which facilitate screening and monitoring of tau deposits in various settings, including developing disease‐modifying therapeutics.